Effect of Distance Education on the Health of Ninth Grade Students - Petko Petkov (Педагогически форум)
Effect of Distance Education on the Health of Ninth Grade Students Author(s): Petko PetkovDOI: 10.15547/PF.2022.024 The article examines the mechanisms of distance learning influence on the health of ninth graders. The opinion of students, their parents and teachers were studied. Reasoned recommendations have been made to minimize the negative effects of this training and to find an optimal solution for the educational process.